Peran Pustakawan dalam Memotivasi Anak Usia Dini Memanfaatkan Layanan Anak di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Suci Lestari; Malta Nelisa (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The purpose of this article is to describe: 1) the role of librarians in motivating kids to utilize children’s services in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat; 2) obstacles encountered in children's services in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat; 3) the efforts made to overcome the problem of children's services at Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat. Data were collected by observation and interview with a librarian in children’s service. Based on the research results in children’s services at Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat, it can be concluded that: 1) lack of the role by librarians because little interaction between librarians with users in children’s services; 2) there are some obstacles such as users still not getting the kinds of children’s services, and lack of understanding by librarians about the importance of librarians in a service at the library; 3) the effort that can be done are add and streamline the kinds of children’s sevices that given to users, complete lack of facilities in children’s services and give the comprehension to librarians about the importance of librarians in a service at the library. Keywords: the role, librarian, motivation, children’s services.